Coconut Shell-Based Briquettes for Sustainable Energy: A Bibliometric Study on Biomass Mixtures and Binder Materials - Darmawan, Ridho; Dewantoro, Awaly Ilham; Mardawati, Efri (Universitas Sanata Dharma, 2025)
Coconut shell is one of the potential biomass resources that has been widely developed as a raw material for briquettes to support renewable energy initiatives and circular economy practices. This study aimed to explore the development, research focus, and future directions of cocomut shell briquette through a systematic literature review. The Methodi Ordinatio approach was employed for analysis, resulting in a final portfolio of 134 selected documents, which were the further examined to identify trends and research gaps. The findings showed that mixturing coconut shell with other biomass such as from wood-based and agricultural-based residues could enhance the briquette performance. Moreover, alternative binders such as lignocellulosic carbohydrate and its derivatives, plant sap, and waste cooking oil offered promising subsitutes for food-based materials. Oily biomass, such as eucalyptus wastes and pine resin, was also found to improve briquette performance due to its volatile content. In addition, the integration of automation technologies based on microcontrolers and the Internet of Things (IoT) began to applied to improve production efficiency and consistency. It is expected that the findings of this study can serve as a foundation for future development focused on material formulation and technological innovations for coconut shell-based briquette production that are more efficient, sustainable, and responsive to future energy needs.